2019
DOI: 10.1063/1.5081915
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of sulfur-containing composites for high-performance lithium–sulfur batteries

Abstract: Sulfur has received considerable attention as a cathode material for lithium− −sulfur (Li− −S) batteries due to its high theoretical energy density (2567 W h kg −1), high earth abundance, and environmental benignity. However, the insulating nature of sulfur and the shuttle effect of soluble lithium polysulfides result in serious technical issues, such as low utilization rate of sulfur, reduced columbic efficiency, and poor cycling stability, which compromise the high theoretical performance of Li− −S batteries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…[6,7] In the last decades, many studies have attempted to integrate sulfur into carbon-based nanostructures to address the problems of low electronic conductivity and shuttle effect. [8][9][10][11][12] The specific capacity of Li-S was increased in the first few cycles because of the improved conductivity obtained by integrating sulfur into the carbon nanostructure. However, the nonpolar surface of carbons was not successful in retaining the dissolution of polar LiPs upon long cycling time.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] In the last decades, many studies have attempted to integrate sulfur into carbon-based nanostructures to address the problems of low electronic conductivity and shuttle effect. [8][9][10][11][12] The specific capacity of Li-S was increased in the first few cycles because of the improved conductivity obtained by integrating sulfur into the carbon nanostructure. However, the nonpolar surface of carbons was not successful in retaining the dissolution of polar LiPs upon long cycling time.…”
Section: Introductionmentioning
confidence: 99%
“…Although these carbon material and polymer matrixs could physically confine related sulfur species and enhance the structural stability, it is not beneficial to the rapid conversion of sulfur and the capacity decay still occur due to the poor interaction between the non‐polar carbon or polymer hosts and the polar LiPSs. [ 22 ] Subsequently, it is confirmed that some polar compounds have the ability of entrapping polysulfides by forming a variety of chemical bonds. Many emerging materials including MnO 2 , [ 23 ] TiO 2 , [ 24,25 ] Co 3 S 4 , [ 26 ] MXene, [ 27 ] CoS 2 , [ 28 ] VO 2 , [ 29,30 ] VN, [ 29 ] BaTiO 3 , [ 31 ] RuO 2 , [ 32 ] Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3 , [ 33 ] and other metal compounds could alleviate the shuttle effect by moderate chemical interaction and promote the redox kinetic process due to their better electrocatalytic activity.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…The reaction between sulfur and unsaturated compound is known as “inverse vulcanization” [ 5 ]. Polysulfides usually exhibit excellent properties preferring them suitable for direct use or as intermediates for further functionalization for various applications [ 15 , 16 ] such as solar cell [ 17 ], hydrogen fuel cell [ 18 ], lithium-ion batteries [ 11 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], high refractive index and IR transmitting optical devices [ 27 , 28 , 29 , 30 ], sulfur-doped carbon materials [ 31 ], heavy metal remediation [ 14 , 31 , 32 , 33 , 34 , 35 ], rubber [ 10 ], fertilizer [ 36 , 37 ], and other advanced materials [ 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%